The Influence of Four Constructs of Social Support on Pregnancy Experiences in Group Prenatal Care - Kalyn M. Renbarger; Jean Marie Place; Melanie Schreiner (Women's Health Reports, 2021)
Objective: This study aimed to identify the influence of the four constructs of social support on positive pregnancy experiences in CenteringPregnancy, a group prenatal care (GPNC) model. Methods: Using a qualitative descriptive design, semi-structured interviews were conducted with 11 women who had participated in at least 6 of 10 GPNC sessions at a family practice medicine residency. Participants were asked to describe their experiences in GPNC. Results: Using a standard content analysis, four constructs of social support (emotional, informational, instrumental, and appraisal) were identified through three major themes: (1) informational support, offered by peers in GPNC settings, promotes learning and prepares women for motherhood; (2) emotional and appraisal support, offered by peers in GPNC, improves emotional well-being and helps women build lasting, supportive connections with peers, and (3) emotional, informational, instrumental, and appraisal support work in tandem to create positive relationships between women and health care providers. Conclusion: Social support provided a means to a positive prenatal health care experience that facilitated the attainment of new knowledge and the formation of positive relationships with health care providers and peers. The findings of this study can provide health care providers with a framework to examine and enhance their practice and care of women in the perinatal period.